2023
DOI: 10.24072/pcjournal.230
|View full text |Cite
|
Sign up to set email alerts
|

Parchment Glutamine Index (PQI): A novel method to estimate glutamine deamidation levels in parchment collagen obtained from low-quality MALDI-TOF data

Abstract: Parchment was used as a writing material in the Middle Ages and was made using animal skins by liming them with Ca(OH) 2 . During liming, collagen peptides containing Glutamine (Q) undergo deamidation resulting in a mass shift of 0.984 Da. Assessing the extent of deamidation can inform us about parchment production patterns and quality. In this study, we propose a simple three-step workflow, developed as an R package called MALDIpqi(), to estimate deamidation in parchment derived collagen using lowresolution M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, research on bone collagen has shown that deamidation does not necessarily correlate with age but is instead dependent on environmental conditions . While little research has been done to understand the effect of ancient tanning methods on collagen deamidation, it has been shown that deamidation of parchment and other skin objects is more dependent on the production techniques and history of the objects than age. , Processes such as liming (dehairing), deliming, and tanning are done under alkali and acidic conditions. Vegetable-tanned leathers have a low pH, which could accelerate deamidation with time.…”
Section: Resultsmentioning
confidence: 99%
“…However, research on bone collagen has shown that deamidation does not necessarily correlate with age but is instead dependent on environmental conditions . While little research has been done to understand the effect of ancient tanning methods on collagen deamidation, it has been shown that deamidation of parchment and other skin objects is more dependent on the production techniques and history of the objects than age. , Processes such as liming (dehairing), deliming, and tanning are done under alkali and acidic conditions. Vegetable-tanned leathers have a low pH, which could accelerate deamidation with time.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it has recently been proposed to use the deamidation grade of glutamine for the calculation of a Parchment Glutamine Index (PQI). However, the focus is not on the time-dependent deamidation, but on the production process, in particular the liming with Ca(OH) 2 , the animal type used, and the thickness, since these factors also have an influence on the deamidation grade [ 166 ].…”
Section: Paleoproteomics and Metaproteomics Analysesmentioning
confidence: 99%